The Influence of Image on Staycation Intention at Dusun Bambu Ecolodge - Humaira, Cyrilla Pratania; Novianti, Syifaa (Politeknik Negeri Bandung, 2024)
The image of a destination significantly impacts tourists' experiences and intentions, particularly in the hospitality and tourism industry. This study examines how the image of Dusun Bambu Ecolodge influences tourists' intention to engage in staycations. Using a quantitative approach, data were collected through questionnaires distributed to 105 respondents who had experienced a staycation at the ecolodge. The analysis employed descriptive and verification statistical techniques, including simple linear regression. The findings reveal that image positively and significantly influences staycation intention, with a correlation coefficient of 0.662 and a determination coefficient of 41%. This indicates that the image variable can explain 41% of the variation in staycation intention, while other factors influence the rest. These results underscore the importance of maintaining and enhancing a positive image to boost staycation intentions. The study highlights practical strategies, including optimizing digital marketing and leveraging social media to promote engaging content and positive visitor experiences. This research contributes to understanding how destination image drives tourist behaviour, offering valuable insights for ecolodge operators and stakeholders in the sustainable tourism sector.